Emerging role of microglia in inter-cellular transmission of α-synuclein in Parkinson’s disease - Zhang, Xiangbo; Yu, Haiyang; Feng, Juan (Frontiers in Aging Neuroscience, 2024)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide, significantly prejudicing the health and quality of life of elderly patients. The main pathological characteristics of PD are the loss of dopaminergic neurons in the substantia nigra (SN) as well as abnormal aggregation of α-synuclein (α-syn) monomers and oligomers, which results in formation of Lewy bodies (LBs). Intercellular transmission of α-syn is crucial for PD progression. Microglia play diverse roles in physiological and pathological conditions, exhibiting neuroprotective or neurotoxic effects; moreover, they may directly facilitate α-syn propagation. Various forms of extracellular α-syn can be taken up by microglia through multiple mechanisms, degraded or processed into more pathogenic forms, and eventually released into extracellular fluid or adjacent cells. This review discusses current literature regarding the molecular mechanisms underlying the uptake, degradation, and release of α-syn by microglia.